2007
DOI: 10.1590/s1517-86922007000300008
|View full text |Cite
|
Sign up to set email alerts
|

Biomarcadores de estresse em ratos exercitados por natação em intensidades igual e superior à máxima fase estável de lactato

Abstract: Introduction:The level of stress during acute /chronic exercise is important, since higher levels of stress may impair animal welfare. The adrenocorticotrophic (ACTH) and corticosterone hormone concentrations, as well as cholesterol and ascorbic acid concentrations in adrenal gland, are considered an important stress biomarker. Purpose: To analyze the sensitivity of the different biomarkers during acute swimming exercise in different intensities performed by rats. Methods: Male Wistar adult rats (n = 18) previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
5
0
6
Order By: Relevance
“…The same was demonstrated by Manchado et al 11 when analyzing the MLSS in Wistar rats submitted to treadmill running and swimming exercise (~3Á9 mmolÁl -1 versus~5Á9 mmolÁl -1 , respectively). In fact, Contarteze et al 26,27 have demonstrated increased levels of stress biomarkers, such as corticosterone and adrenocorticotropic hormones, in rats submitted to swimming exercise when compared with running mice.…”
Section: Discussionmentioning
confidence: 99%
“…The same was demonstrated by Manchado et al 11 when analyzing the MLSS in Wistar rats submitted to treadmill running and swimming exercise (~3Á9 mmolÁl -1 versus~5Á9 mmolÁl -1 , respectively). In fact, Contarteze et al 26,27 have demonstrated increased levels of stress biomarkers, such as corticosterone and adrenocorticotropic hormones, in rats submitted to swimming exercise when compared with running mice.…”
Section: Discussionmentioning
confidence: 99%
“…The animals performed the training with frequency of five days per week (one hour/day), supporting load equivalent to 2% of their body weight attached to their torsos, during eight weeks, with beginning at 90 days old. The 2% of their body weight intensity used in the present study may be considered light to moderate or subliminary, since it is already well-established that the load equivalent to the aerobic/anaerobic metabolic transition (anaerobic threshold) is obtained in average at 5% of body weight from the application of different tests adapted to the rat conditions during the swimming exercise 10 .…”
Section: Dietmentioning
confidence: 99%
“…Studies show that cortisol secretion increases with the intensity of the physical activity. High-intensity exercise increases the activity of stress hormones, such as cortisol, adrenocorticotropic hormone (ACTH), and catecholamines (norepinephrine, epinephrine, and dopamine) [37,38]. The increase of these hormones may inhibit synthesis and stimulation of protein degradation, and consequently lead to their breakdown in skeletal muscles [39].…”
Section: Discussionmentioning
confidence: 99%